Kedudukan Hukum Perbankan Syariah dalam Sistem Perbankan Nasional - Titik Triwulan Tutik (IAIN Salatiga, 2016)
The development of Islamic banks as part of the Islamic economic system inIndonesia can be said late compared to that in other countries whose populationis predominantly Muslim. However, the legal position of Islamic banking isjuridically strong and aligned with other conventional banks. If a dispute occursto those banks, according to the decision of Constitutional Court No. 93/PUU-X/ 2012 stating that it can be solved using two ways, namely, litigation and non-litigation. Problem solving using way of litigation becomes the absolute uthority of religious courts, while problem solving using nonlitigation, each party may choose the solution which is not only that explained on Article 55 paragraph (2) of Law No. 21 of 2008 concerning Islamic Banking, but it can also take other alternatives according to the deal made. Surveillance towards Islamic Banking is held not only by insider but also by independent regulatory institution namely DPS and DSN that both have duty of maintaining the Islamic banking towards an ideal situation and keep the Muslims. In addition, as a form of public participation, all Muslims have an obligation to conduct surveillance towards Islamic banking either directly or indirectly as a vehicle for commanding the good and forbidding dishonor towards the implementation of Islamic banking as the Islamic economic life